The AI revolution in medicine GPT-4 and beyond - Lee, Peter; Goldberg, Carey; Kohane, Isaac; Bubeck, Sébastien (Pearson, 2023)
Just months ago, millions of people were stunned by ChatGPT's amazing abilities -- and its bizarre hallucinations. But that was 2022. GPT-4 is now here: smarter, more accurate, with deeper technical knowledge. GPT-4 and its competitors and followers are on the verge of transforming medicine. But with lives on the line, you need to understand these technologies -- stat. What can they do? What can't they do -- yet? What shouldn't they ever do? To decide, experience the cutting edge for yourself. Join three insiders who've had months of early access to GPT-4 as they reveal its momentous potential -- to improve diagnoses, summarize patient visits, streamline processes, accelerate research, and much more. You'll see real GPT-4 dialogues -- unrehearsed and unfiltered, brilliant and blundering alike -- all annotated with invaluable context, candid commentary, real risk insights, and up-to-the-minute takeaways.
Includes bibliographical references. - Description based on print version record
Keywords: Artificial intelligence -- Medical applications; Intelligence artificielle en médecine; Artificial intelligence; Medical applications